2017
DOI: 10.3311/ppch.10805
|View full text |Cite
|
Sign up to set email alerts
|

Bio-produced Propionic Acid: A Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The three different biochemical pathways for propionate production include the succinate, acrylate, and propanediol pathways (Reichardt et al, 2014; Vidra & Németh, 2018). Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…The three different biochemical pathways for propionate production include the succinate, acrylate, and propanediol pathways (Reichardt et al, 2014; Vidra & Németh, 2018). Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered that microorganisms concentrated more energy on butyrate production than acetate production upon SFR, which was also supported by the increased abundances of butyrate-producing bacteria Pseudobutyrivibrio and Papillibacter. Propionate is mainly produced via the succinate pathway (from pyruvate to succinate and then to propionate) and the acrylate pathway (using acrylate and lactate as substrates) [ 30 , 31 ]. We found that propionate production through the acrylate pathway was probably increased while that through the succinate pathway was weakened under SFR condition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the enhanced methanogenesis in SFR ewes was in agreement with the report by Goopy et al [ 32 ] who found that severe below-maintenance feed intake increased methane yield in cattle. As well-known that methanogenesis competes the same substrates such as hydrogen with propionate production [ 31 , 33 ]. Thus, the enhanced methanogenesis suggests that malnutrition may exclude propionate-producing functional groups [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For industrial purposes, propionate is synthesized by petrochemical means—Reppe and Larson processes. The Reppe process involves the conversion of ethylene, carbon monoxide, and steam into propionic acid, while in the Larson process, propionic acid is produced from ethanol and carbon monoxide in the presence of a catalyst (boron trifluoride) [ 2 , 3 ]. Propionic acid is used primarily in the food and feed industry as a preservative for inhibiting the growth of yeasts and molds.…”
Section: Introductionmentioning
confidence: 99%